1998
DOI: 10.1523/jneurosci.18-10-03749.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Neuronal Form of the Cell Adhesion Molecule L1 Contains a Tyrosine-Based Signal Required for Sorting to the Axonal Growth Cone

Abstract: The neural cell adhesion molecule L1, which is present on axons and growth cones, plays a crucial role in the formation of major axonal tracts such as the corticospinal tract and corpus callosum. L1 is preferentially transported to axons and inserted in the growth cone membrane. However, how L1 is sorted to axons remains unclear. Tyr 1176 in the L1 cytoplasmic domain is adjacent to a neuron-specific alternatively spliced sequence, RSLE (Arg-Ser-Leu-Glu). The resulting sequence of YRSLE conforms to a tyrosine-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
81
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 62 publications
4
81
0
Order By: Relevance
“…We previously reported that predominantly the neural form of L1 containing the RSLE form is recruited in spontaneously released vesicles (24). The RSLE motif facilitates interaction with the A2 chain of the clathrin adaptor AP-2 and affects the phosphorylation and endocytosis of L1 by creating an endocytic motif allowing clathrin-mediated internalization (49,50). Indeed, we found by reverse transcription-PCR that OVMz cells expressed the neural form of L1.…”
Section: Discussionmentioning
confidence: 86%
“…We previously reported that predominantly the neural form of L1 containing the RSLE form is recruited in spontaneously released vesicles (24). The RSLE motif facilitates interaction with the A2 chain of the clathrin adaptor AP-2 and affects the phosphorylation and endocytosis of L1 by creating an endocytic motif allowing clathrin-mediated internalization (49,50). Indeed, we found by reverse transcription-PCR that OVMz cells expressed the neural form of L1.…”
Section: Discussionmentioning
confidence: 86%
“…ALCAM does not possess any sorting signals targeting the protein to the axonal compartment, such as found for CAML1 (Kamiguchi and Lemmon, 1998;Yap et al, 2008); we therefore asked whether ALCAM might be synthesized in the axon tip (growth cone). Translation in the axonal growth cone has been shown for approximately ten different proteins (Jung and Holt, 2011) and is required for the response to various guidance cues (Lin and Holt, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Second, L1 adhesion may be regulated at the level of cell surface expression (17). The neuronal form of L1 contains an alternatively spliced exon encoding four amino acids (RSLE) within the L1CD (18), which contributes to a tyrosine based sorting/endocytosis motif (YRSL) (19). This sequence enables the L1CD to directly bind the 2 subunit of the adaptin complex AP-2, linking L1 to the clathrin-mediated endocytotic pathway (20).…”
mentioning
confidence: 99%